Psychometric Properties and Gender Invariance of the Positive Mental Health Scale in Spanish Nurses During the COVID‐19 Pandemic - María Auxiliadora Robles‐Bello; David Sánchez‐Teruel; Selma Boufellous; Cristina Lendínez‐Rodríguez (Nursing Open)
ABSTRACT Aim Positive mental health (PMH) can be considered a key aspect of mental health in the face of potentially stressful healthcare situations such as the COVID‐19 pandemic. The aim of this study was to analyse the psychometric properties of the Spanish version of the Positive Mental Health Scale (PMS) in Spanish nurses during the COVID‐19 pandemic. Design Descriptive analysis, confirmatory factor analysis, gender invariance analysis and convergent and divergent analyses were performed, and reliability indices were calculated. Methods A total of 661 nurses (425 women and 236 men) participated in the study. They completed various questionnaires during August–October 2021. Results Factor analysis demonstrated a unidimensional structure with very good indices of model fit, high positive convergent validity, especially with social support, self‐efficacy and resilience to suicide attempts, and high divergent validity with anxiety and, to a lesser extent, with depression. There was also strong invariance between genders and high reliability indices. In conclusion, the data show that the PMS has adequate validity and reliability in nurses. Furthermore, this study allows us to confirm gender invariance, which has not been examined in other studies. The data show that PMS is a suitable measure for assessing the mental health of healthcare professionals exposed to high‐stress situations. Patient or Public Contribution No patient or public contributions.